2010
DOI: 10.1016/j.ejrad.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma treated with postoperative radio-chemotherapy: Prognostic value of apparent diffusion coefficient at MR imaging

Abstract: The ADC(MIN) value obtained from pretreatment MR images is a useful clinical prognostic biomarker in patients with glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…Several reasons may be offered as explanations. First, the discrepancy between the present study and those results observed in primary CNS tumours [27][28][29] may also be owing to histopathological differences between different tissue types. Second, there can be biological differences between primary lesions and metastatic deposits [30].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Several reasons may be offered as explanations. First, the discrepancy between the present study and those results observed in primary CNS tumours [27][28][29] may also be owing to histopathological differences between different tissue types. Second, there can be biological differences between primary lesions and metastatic deposits [30].…”
Section: Discussioncontrasting
confidence: 54%
“…In fact, these histological features have been shown to adversely influence survival [22][23][24][25][26]. In malignant astrocytoma [27], glioblastoma [28] and primary central nervous system (CNS) lymphoma [29], a lower pre-treatment ADC has been shown to be associated with improved survival. However, the ability of ADC values in predicting survival in extracranial tumours and metastatic lesions has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the ADC has been shown to correlate also with prognosis and treatment responses in patients with high-grade gliomas. In particular, a low pretreatment ADC value predicts a less favorable prognosis if compared with higher values [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature on the use of ADC in brain tumors reports the use of a single ADC threshold to distinguish high ADC, due to low cellularity vasogenic edema and necrosis from intermediate ADC, due to high cellularity tumor [30]. In addition to typical high ADC necrosis, an additional form of necrosis—sometimes referred to as “gelatinous necrosis”—has been described, characterized by very low ADC in the area of necrosis [19, 29].…”
Section: Discussionmentioning
confidence: 99%